Contribuição ao conhecimento químico de plantas do nordeste do Brasil: avaliação biológica e estudo fitoquímico de Tephrosia cinerea Pers. (Fabaceae) - Malcher, Grazielle Tavares (2007)
This work reports the phytochemical study of Tephrosia cinerea Pers., Fabaceae, popularly known as "anil bravo". This plant is used to paralyze fish due to its ictiotoxic activity [...]